Combatting burnout : a guide for medical students and junior doctors - Staten, Adam (Boca Raton, FL : CRC Press/Taylor & Francis Group, 2019)
This timely aid, filled with 'down to earth' advice, provides invaluable guidance on avoiding burnout and on how to combat it should it occur. The book offers innovative ways to change working practices, shares advice on building protective mechanisms into daily working life and explores the diverse array of career options that are available to doctors. Key features: The first practical guide to help medical students and junior doctors identify, combat and avoid burnout Recognises and describes the impact that burnout has on the ability of doctors to work safely and of students to study effectively, and the impact burnout has on the wider healthcare system Discusses the factors that affect resilience and how this can be nurtured, and where help can be found for those who feel they are experiencing burnout Enhanced by 'real life' examples throughout Addressing the growing body of evidence that highlights burnout as an increasing problem among medical students and junior doctors worldwide, with a lasting impact on those directly affected, on the wider workforce and entire healthcare systems, this book will enable readers to identify and address problems quickly and see how they can build careers that are personally satisfying.
What is burnout? / Dr Adam Staten & Dr Mike Forsythe -- Pressures of the job / Dr Mike Forsythe -- External pressures / Dr Cristina Costache & Dr Adam Staten -- Medical school burnout / Dr Jonathan C.H. Lau & Dr Ashton Barnett-Vanes -- Changing the way we work / Dr Adam Staten -- Finding a voice / Dr Adam Staten, Dr Duncan Shrewsbury, Dr Elizabeth Waters-Dapre & Dr Ben Balogun -- Finding the right career / Dr Adam Staten -- Resilience / Dr Euan Lawson -- Interventions and seeking help / Dr Fiona Day -- Final thoughts / Dr Adam Staten.
OCLC-licensed vendor bibliographic record.
Keywords: Medical education; Medical students -- Psychology; HEALTH & FITNESS / Holism; HEALTH & FITNESS / Reference; MEDICAL / Alternative Medicine; MEDICAL / Atlases; MEDICAL / Essays; MEDICAL / Family & General Practice; MEDICAL / Holistic Medicine; MEDICAL / Osteopathy; MEDICAL / General; MEDICAL / Internal Medicine; MEDICAL / Surgery / General